Pengaruh Direct Selling Dan Service Quality Terhadap Keputusan Orang Tua Pada Penerimaan Peserta Didik Baru Mi Tahfizh Nurul Qur’an Padang Yang Dimediasi Oleh Word Of Mouth (WOM) - Peni Andesta; Eka Mariyanti (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
This study investigates the influence of direct selling and service quality on parents’ decisions in selecting MI Tahfizh Nurul Qur’an Padang, with word of mouth (WOM) acting as a mediating variable. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed, involving 150 respondents obtained through convenience sampling. Results reveal that direct selling and service quality significantly affect parents’ decisions, both directly and indirectly through WOM. The Q²_predict values for WOM (0.048) and parents’ decision (0.010) indicate the model’s predictive relevance. These findings underscore the importance of effective personal selling and high service standards in enhancing parental decision-making in educational settings.